Changes in antiretroviral therapy guidelines: implications for public health policy and public purses. Issue 5 (28th September 2010) - Hamilton, Alex; Garcia-Calleja, Jesus M; Vitoria, Marco; Gilks, Charles; Souteyrand, Yves; De Cock, Kevin; Crowley, Siobhan
Abstract : Introduction: The World Health Organization (WHO) published a revision of the antiretroviral therapy (ART) guidelines and now recommends ART for all those with a CD4 cell count ≤350/mm 3, for people with HIV and active tuberculosis (TB) or chronic active hepatitis B irrespective of CD4 cell count and all HIV-positive pregnant women. A study was undertaken to estimate the impact of the new guidelines using four countries as examples. Methods: The current WHO/UNAIDS country projections were accessed based on the 2007 estimates for Zambia, Kenya, Cameroon and Vietnam. New projections were created using Spectrum. CD4 progression rates to need for ART were modified and compared with the baseline projections. Results: The pattern of increased need for treatment is similar across the four projections. Initiating treatment at a CD4 count <250/mm 3 will increase the need for treatment by a median of 22% immediately, initiating ART at a CD4 count <350/mm 3 increases the need for treatment by a median of 60%, and the need for treatment doubles if ART is commenced at a CD4 count <500/mm 3 . Initiating ART at a CD4 cell count <250/mm 3 would increase the need for treatment by a median of around 15% in 2012; initiating treatment at a CD4 count <350/mm 3 increases the need for treatment by a median of 42% across the same projections and about 84% if CD4 <500/mm 3 was used. Conclusions: The projections indicate that initiating ART earlier in the course of the disease by increasing the threshold for the initiation of ART would increase the numbers of adults in need of treatment immediately and in the future.